TAFSSA webinar session 12: Who does what within the household? - Transforming Agrifood Systems in South Asia (TAFSSA) (International Maize and Wheat Improvement Center, 2024)
This is part of TAFSSA’s 2024 webinar series to highlight the research findings based on a comprehensive sub-national agrifood systems assessment conducted in early 2023 in rural areas of five districts across Bangladesh, India and Nepal.